What Is the Impact of a Community Orthopaedic Triage Service in the Management of Hip and Knee Osteoarthritis in the New Zealand Public Health System? - Stilwell, Jennifer Ann (Auckland University of Technology, 2023)
Background: Osteoarthritis (OA) is a worldwide highly prevalent disease that causes loss of function, disability, and pain. Despite the prevalence and financial burden of the disease, the New Zealand public health system has yet to adopt a national model of care for OA management. One of the key goals of New Zealand Better, Sooner, More Convenient Care draws attention to freeing up highly trained health professionals to focus on the most complex patient. This involves training other health professionals to complete simpler tasks that would otherwise have been done by a doctor or senior medial professional. Advanced Practice Physiotherapists (APP) are physiotherapists that have undertaken advanced training and potentially specialisation in a particular area of physiotherapy. These APPs have the ability to examine, provide early conservative management strategies and reassurance to patients that are currently referred to orthopaedic surgeons. OA models of care led by APPs who specialise in orthopaedics, have long been implemented in health care systems around the world but are a new concept for New Zealand District Health Boards. The implementation of the Community Orthopaedic Triage Service (COTS) within the Bay of Plenty District Health Board (BOPDHB) was established as part of a larger orthopaedic transformation project to improve the patient journey through the public health system by providing earlier assessment and onward referral to the most appropriate intervention for patients with OA of the hip and knee. Aim: This study evaluated the impact of the COTS in the management of hip and knee OA directly to patients, staff, and stakeholders within the New Zealand public health system. Methods: A pragmatic mixed methods evaluation was undertaken. Part one included a retrospective audit of outcome variables from APP led orthopaedic assessments and part two included prospectively collected data in the form of semi-structured interviews from patients, staff and stakeholders. Data was analysed using descriptive statistics and thematic analysis and then triangulated for further discussion. Results: Results demonstrate that the COTS could manage 49-52% of the volume of patients referred to orthopaedic outpatients within a 12-month time period. There was a higher percentage of patients reported as Māori seen in the COTS compared to those seen in orthopaedics. The COTS had a lower wait time of 37 days as opposed to 158 days to be seen in orthopaedics. ANOVA comparing the 3 groups shows statistically significant difference (p-value<0.0001) in mean waiting times across the 3 groups. Eighty per cent of patients referred for an orthopaedic First Specialist Appointment (FSA) from the COTS received appropriate orthopaedic management. Data analysis of the interviews resulted in one central organising concept: Changing the narrative about OA care delivery in the New Zealand Public Health System. This concept is entwined within three main themes: Making OA a national health priority, optimisation of public health resources and embedding best practice. The triangulated data found multiple benefits of the COTS to patients regarding their hip or knee care trajectory including improved experience, access to earlier intervention and increased satisfaction. The COTS also has direct impact to the DHB as an organisation, to its physiotherapy workforce and to GPs including bridging the gap between primary and secondary care, providing musculoskeletal support and utilising physiotherapy at top of scope. The study has highlighted positive impacts of the COTS directly to the orthopaedic workforce including improving conversion rate to surgery and providing an equal playing field. However, data reports some negative impacts of the COTS including its potential to increase surgical workload on orthopaedics unless additional surgical resources are provided to allow the surgeon to shift from clinic into the operating theatre. There were further concerns that the pathway may impact access by merely shifting the waiting list from orthopaedics to COTS, subsequently having no intended benefit to the patient. Further work needs to be undertaken to determine the impact of the COTS in its ability to impact orthopaedic workload and freeing up surgeon time in the longer term. To maximise its impact, the DHB needs to consider fostering meaningful relationships with orthopaedic surgeons, support clinicians in ongoing education and engage with GPs to raise the profile of the service. Conclusion: This study contributes to a better understanding to the beneficial impact of an APP led model of care for hip and knee OA including how it affects experience, waiting times, quality of care and resource use. Further research is needed to strengthen the impact of this model in freeing up surgeons, enhancing more surgeries and spending less time with initial assessment. The COTS is a pragmatic and evidence-based model of care for OA and should be considered by the Ministry of Health as a new way of working in the management of orthopaedic patients.